Generalized Pinch Analysis Scheme Using MATLAB. Issue 3 (March 2015) - Tewari, Kshitij; Agrawal, Sumit; Kumar Arya, Raj
Abstract In pinch analysis, the calculations needed for determining pinch temperatures and minimum utility requirements are simple and can be done manually in case of a small number of streams. However, in real‐scale industrial problems, the calculation can become tedious and very much time‐consuming. A generalized low‐cost and user‐friendly scheme for pinch design using MATLAB is proposed. This scheme is tested for several problems for accuracy and robustness to determine hot pinch temperature, cold pinch temperature, minimum cooling load, and minimum heating load using the temperature interval method. The solutions developed by the proposed scheme are mirror images of solutions found by applying a rigorous procedure.